ANALYSIS OF THE IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTING FROM A SHARIA PERSPECTIVE TO SUPPORT THE SUSTAINABLE DEVELOPMENT GOALS IN ECOTOURISM SUSTAINABILITY - Nessa Anggi Sahputri; Annio Indah Lestari Nasution; Yenni Samri Juliati (JAT : Journal Of Accounting and Tax, 2026)
This study aims to analyze the implementation of environmental accounting from a Sharia perspective in ecotourism management and its relation to supporting the achievement of the Sustainable Development Goals (SDGs) at Bukit Lawang Nature Tourism, Langkat Regency, North Sumatra. This research employs a qualitative approach with data collection techniques conducted through interviews, observations, and documentation involving managers, local communities, and visitors. The results of the study indicate that environmental management has been carried out through various activities such as waste management, maintaining river cleanliness, and environmental maintenance. However, the implementation of environmental accounting is still at an early stage because environmental costs have not been recorded separately and systematically, and there is no formal environmental budgeting system in place. From a Sharia perspective, environmental management practices have reflected the values of trustworthiness (amanah) and responsibility as khalifah in preserving nature, although the implementation of environmental accounting has not yet been fully integrated as a decision-making tool. Therefore, the development of a more structured environmental accounting system is needed to enhance transparency, accountability, and support the sustainability of ecotourism as well as the achievement of the SDGs.